AN ANALYSIS ON 11 GRADERS’ DIFFICULTIES IN LEARNING CONDITIONAL SENTENCES AT SMA XAVERIUS BANDAR LAMPUNG - Novi Yanti; Susanto Susanto (Universitas Bandar Lampung, 2017)
This study is conducted as its objectives to analyze the eleventh graders difficulties including the cause of the difficulties since it seems like the students hard to deeal with conditional sentences. In this study, the researcher used descriptive qualitative method to describe the others’ point of views of particular phenomena. It wa also used to get the truthful, precise, and well organised explanation about students’ difficulties and the cause if the diffivulties in dealing with English conditionals. The research wa done at Grade 11 SMA Xaverius Bandar Lampung. To collect the data, I did observations and interview. The data collected wa analyzed by combining the result of the observation and interview ( both the students and the teacher ) ina number of paragraphs. The result of this study showed the conditional sentences are difficult in meaning, form, and the tense. The major causes for the students’ difficulties are because of grammar and vocabulary lackness. They have priblems in translating certain English words into Indonesian language. Morover, the form conditional sentences which requires grammar understanding also seemed like additional troublesome for the students when they learn conditional sentences.